Efficient static and dynamic removal of Sr(II) from aqueous solution using chitosan ion-imprinted polymer functionalized with dithiocarbamate. Issue 2 (June 2015) - Liu, Fangfang; Liu, Yan; Xu, Yan; Ni, Liang; Meng, Xiangguo; Hu, Zhaoyong; Zhong, Guoxing; Meng, Minjia; Wang, Yun; Han, Juan
Abstract: A novel chemically modified chitosan Sr(II)-imprinted polymer (Sr(II)-IIP) with dithiocarbamate groups was prepared. The adsorbent was characterized by FT-IR, XPS, SEM and nitrogen adsorption–desorption. Sr(II)-IIP has regular spherical geometry and possesses larger surface area, pore volume and average pore diameter as compared to those of chitosan. Batch adsorption experiments were performed to evaluate the adsorption conditions and selectivity. The results showed that the maximum static adsorption capacity of Sr(II)-IIP for Sr(II) was 86.66 mg g −1 at 45 °C, which was larger than many other adsorbents. The experimental data were in good agreement with pseudo-second-order and Langmuir isotherm model. A continuous fixed-bed column study on Sr(II)-IIP showed that the adsorption capacity increased with increasing influent concentration, but decreased with increasing bed depth, flow rate and temperature. The mechanism for dynamic adsorption of Sr(II) onto Sr(II)-IIP was found to follow the Thomas model. Sr(II)-IIP was regenerated and found to be suitable for reuse in successive adsorption–desorption cycles seven times without significant loss in adsorption capacity, which showed that this novel adsorbent could be employed as an effective material for the selective removal of Sr(II) from aqueous solutions.